2006
DOI: 10.1248/bpb.29.1234
|View full text |Cite
|
Sign up to set email alerts
|

Delay of Cataract Development in the Shumiya Cataract Rat by the Administration of Drinking Water Containing High Concentration of Magnesium Ion

Abstract: Mineral ion, an essential element, plays a very important biochemical role in the body. It has been recognized that mineral ion imbalance is associated with several major diseases, such as diabetes mellitus, hypertension, cardiovascular and cerebrovascular diseases and heart infarction. [1][2][3][4][5][6][7] In addition, Iwata and Kinoshita reported mineral ion imbalance in the lens causes cataract. 8,9) Any alteration in the optical homogeneity of the lens or decrease in its transparency is known as a catarac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…[18][19][20][21][22][23] Recently, we reported that appropriate supplementation of Mg 2ϩ suppressed the decrease of Mg 2ϩ concentration and the increase of Ca 2ϩ concentration in SCR rat lenses, resulting in delayed cataract development. 24) These findings suggest that the Mg 2ϩ concentration in the lens relates to the progression of lens opacification. In this study, we investigated the effect of Mg 2ϩ deficiency on NO production, the ATP level and ATPase activity in HLE cells.…”
Section: Discussionmentioning
confidence: 92%
“…[18][19][20][21][22][23] Recently, we reported that appropriate supplementation of Mg 2ϩ suppressed the decrease of Mg 2ϩ concentration and the increase of Ca 2ϩ concentration in SCR rat lenses, resulting in delayed cataract development. 24) These findings suggest that the Mg 2ϩ concentration in the lens relates to the progression of lens opacification. In this study, we investigated the effect of Mg 2ϩ deficiency on NO production, the ATP level and ATPase activity in HLE cells.…”
Section: Discussionmentioning
confidence: 92%
“…Photographs of the lens were taken using a dark-field set up with illumination from a circular light situated above the lens by microscope equipped with a CCD camera (Olympus, Japan). The outline of the lens image was determined by selecting 4 points on the image, and then the transparent area within the outline and thread level were set automatically by the software ( 21 ). The total area of opacity, in pixels, was analyzed by a computer using Image Pro Plus system (Media Cybernetics, USA).…”
Section: Chemicalsmentioning
confidence: 99%
“…The biological functions of DSW have been investigated for various uses, including attenuating hyperlipidaemia, as well as atherosclerosis, dermatitis syndrome and allergic skin responses (Hataguchi, Tai, Nakajima, & Kimata, 2005;Kimata, Tai, & Nakajima, 2001;Miyamura et al, 2004;Ueshima, Fukao, Okada, & Matsuo, 2003;Yoshioka et al, 2003). Nagai et al (2006) indicated that intake of Mg from DSW delays cataract development in the shumiya cataract rat. Ouchi et al (1990) indicated that dietary Mg prevents atherosclerosis in rabbits fed a cholesterol-enriched (1%) diet.…”
Section: Introductionmentioning
confidence: 99%